Examining Students’ Perception and Motivation on the Content-based Instruction (CBI) Implementation in Vocational Education - Sharizan, Sharizan; Titania, Fani Nabila; Rihatmi, Rihatmi; Handayani, Riris; Sukarno, Sukarno; Musaldin, La Ode; Sadiyah, Noviachri Imroatul (JOLLT Journal of Languages and Language Teaching, 2024)
Content-based Instruction (CBI) uses authentic materials and language as a medium for teaching English. It aligns with the ESP concept in vocational education and might affect students’ perception and motivation. This study assessed vocational high school students’ perception and motivation toward CBI implementation in teaching English. The case study involved 35 students of the 10.2 Culinary Arts Major class, SMK Negeri 2 Godean, Sleman Yogyakarta. The study was started from March to June 2024. The samples were determined through the purpose sampling technique, which involved all the participants as samples. Then, the instruments being used were validated questionnaires (a Pearson correlation value of 0.445 to 0.877 and a Cronbach alpha value of 0.997) supported by open-ended questions and classroom observation. The results showed that vocational high school students have a moderate level of perception (3.31) and motivation (3.44) on CBI implementation based on the Likert Scales’ interpretation. However, the students have a high perception of the authentic materials being used and instrumental motivation about the importance of English in their lives. This leads them to have a willingness to learn English. It is supported by their positive responses to open-ended questions and nuances in classroom observation. Meanwhile, it is vital to maintain internal motivation and be assertive in implementing CBI by applying clear learning objectives and contracts to make a conducive classroom. Finally, due to participants’ limitations, conducting future studies with broader participants, including teachers and students from other majors, is crucial.